The waiting time of admission to operation was associated with preoperative deep vein thrombosis in geriatric hip fracture - Wen-Si Qiang; Lu Dang; Yi-Lun Wu; Bin-Fei Zhang (Scientific Reports)
Abstract This study evaluated the association between admission to operation (ATO) time and preoperative deep vein thrombosis (DVT) in geriatric hip fractures under anticoagulation and mechanical thromboprophylaxis. Geriatric patients with hip fractures were screened between January 2015 and September 2019. We collected demographic information and DVT screening results from the medical system. Multivariate binary logistic regression and generalized additive models were used to identify the linear and non-linear associations between ATO and preoperative DVT. Also, we performed Propensity Score Matching (PSM) to test the robustness of our results in a real-world study. This study included one thousand seven hundred and thirty-five patients. There were 443, 726, and 566 patients in ATO ≤ 2d, 2d < ATO ≤ 4d, and ATO > 4d groups, respectively. Preoperative DVT occurred in 543 (31.3%) patients. There was a “J” type in curve fitting, and the result showed a curvilinear relationship between ATO and preoperative DVT. ATO of 3d was the inflection point. ATO increasing was not associated with an increase of preoperative DVT when ATO < 3d (OR = 0.83; 95%CI: 0.66–1.03; P = 0.09), whereas ATO increasing was associated with DVT (OR = 1.08; 95%CI: 1.04–1.14; P < 0.01) at ATO > 3d. In a real-world population of 1:1 under PSM, we found that the results were stable and the inflection point was the same as the total population. ATO is nonlinearly associated with preoperative DVT in geriatric patients with hip fractures under anticoagulation and mechanical thromboprophylaxis. The 3d was the important point in DVT formation. Each one-day increase in ATO was associated with an 8% increase in the incidence of preoperative DVT when ATO > 3d. Study Registration: This study was registered on the website of the Chinese Clinical Trial Registry (ChiCTR: ChiCTR2200057323).